Impaired synaptic incorporation of AMPA receptors in a mouse model of fragile X syndrome - Chojnacka, Magdalena; Beroun, Anna; Magnowska, Marta; Stawikowska, Aleksandra; Cysewski, Dominik; Milek, Jacek; Dziembowska, Magdalena; Kuzniewska, Bozena (Frontiers in Molecular Neuroscience, 2023)
Fragile X syndrome (FXS) is the most common monogenetic cause of inherited intellectual disability and autism in humans. One of the well-characterized molecular phenotypes of Fmr1 KO mice, a model of FXS, is increased translation of synaptic proteins. Although this upregulation stabilizes in adulthood, abnormalities during the critical period of plasticity have long-term effects on circuit formation and synaptic properties. Using high-resolution quantitative proteomics of synaptoneurosomes isolated from the adult, developed brains of Fmr1 KO mice, we show a differential abundance of proteins regulating the postsynaptic receptor activity of glutamatergic synapses. We investigated the AMPA receptor composition and shuttling in adult Fmr1 KO and WT mice using a variety of complementary experimental strategies such as surface protein crosslinking, immunostaining of surface receptors, and electrophysiology. We discovered that the activity-dependent synaptic delivery of AMPARs is impaired in adult Fmr1 KO mice. Furthermore, we show that Fmr1 KO synaptic AMPARs contain more GluA2 subunits that can be interpreted as a switch in the synaptic AMPAR subtype toward an increased number of Ca2+−impermeable receptors in adult Fmr1 KO synapses.